The Use of Chopsticks as a Cultural Identity of Chinese Society - Ubra, Gaby Agustina; Pasang, Kezia Yansen; Ningsih, Tri Wahyu Retno (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the types of chopsticks that are known by research informants and the use of chopsticks, which is a cultural identity of the Chinese community and ethnic Chinese, especially in the cities of Shandong and Jakarta. The research method used is a qualitative ethnography method. Data collection techniques using observation, interviews, and documentation. The data analysis process uses steps, namely, data reduction, data presentation, and verification. Based on the results of the analysis of the types of chopsticks known to the Chinese ethnic community in Jakarta and the Chinese community in Shandong, among others, bamboo chopsticks, stainless steel chopsticks, wooden chopsticks, plastic chopsticks, ivory chopsticks, silver chopsticks, and gold chopsticks. There are three aspects of cultural identity that appear in this study, namely individual identity, family identity, and belief identity. Individual identity is indicated by the freedom to use chopsticks as their identity wherever they are. Family identity arises from the habit or tradition of a large family to eat together at the dining table and use chopsticks as an identity in the family. The identity of the belief shows the use of chopsticks in the place of prayer, which is used for ancestral ceremonies.